ESTABLISHING THE HOURLY AND OPTIMAL ENERGY BALANCE FOR THE KAESER CSD102.55 KW HELICAL SCREW COMPRESSOR - Andreea TATARU; Dan Codrut PETRILEAN (Fiabilitate şi Durabilitate)
In the article, the real and optimal hourly thermal energy balance of the helical compressor was conceived. Through a technically feasible measure, the specific consumption of the helical compressor was reduced, and the effective heat recovered was then calculated.